EFEKTIVITAS SENAM HAMIL TERHADAP PENURUNAN KECEMASAN PRIMIGRAVIDA : LITERATUR REVIEW - Sartika Sartika (Jurnal JKFT, 2025)
Background: Pregnancy is a physiological process in pregnant women during the reproductive period. Changes in psychological function experienced by pregnant women, it can be a psychological problem for pregnant women and postpartum mothers, one of which is anxiety. This literature review aims to determine the effectiveness of pregnancy exercise on reducing anxiety in primigravida. Methods: descriptive analytical approach to literature review. Sources of data were obtained from the search results and selection of articles using the pubmed database, google schooler and Microsoft academic. The purpose of the article is identified to meet the following criteria:; 1) mild, moderate, and severe anxiety; 2) pregnancy exercise intervention; 3) published in the 2011-2021 range; 4) speak English and Indonesian; 5) have full text; 6) experimental study design. The total sample is 112 respondents. The analysis used a map of extracted data in a grid synthesis table including author, year of publication, country, objectives, sample size, design, type and duration of intervention, results and conclusions of the study. Results: Of the 4 articles reviewed, all studies reported that pregnancy exercise can reduce anxiety in primigravida mothers. Conclusion: pregnant exercise can significantly reduce anxiety in primigravida mothers, therefore, it is suggested to primigravida mothers to be able to do pregnancy exercise to reduce anxiety felt during pregnancy.keywords: pregnancy, anxiety, pregnancy exercise